SISTEM INFORMASI AKUNTANSI DANA KAS KECIL PADA PT. PEGADAIAN (PERSERO) CABANG PURWOREJO BERBASIS WEB - Febri Setyawati; Imam Tri Suryadin (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
PT. Pegadaian (Persero) Purworejo Branch, this is a non-bank financial institution engaged in services that incarryingout its operational activities can not be separated from the use of cash, both the formation of petty cash funds, refillpetty cash fund balances and petty cash expenditure. Viewed from the service side of PT. Pegadaian Purworejo Branchhas been very good, but on the side of the petty cash recording is still lacking, this is because financial records still useMicrosoft excel so it is prone to errors.